2020
DOI: 10.3390/molecules25071617
|View full text |Cite
|
Sign up to set email alerts
|

Phytostabilization of Pb-Zn Mine Tailings with Amorpha fruticosa Aided by Organic Amendments and Triple Superphosphate

Abstract: A greenhouse pot trial was conducted to investigate the effect of organic amendments combined with triple superphosphate on the bioavailability of heavy metals (HMs), Amorpha fruticosa growth and metal uptake from Pb-Zn mine tailings. Cattle manure compost (CMC), spent mushroom compost (SMC) and agricultural field soil (AFS) were applied to tailings at 5%, 10%, 20% and 30% w/w ratio, whereas sewage sludge (SS) and wood biochar (WB) were mixed at 2.5%, 5%, 10% and 20% w/w ratio. Triple superphosphate (TSP) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 113 publications
1
9
0
Order By: Relevance
“…Similar, fluctuations were documented by incubation and pot experiment studies ( El-Mahrouky et al, 2015 , Zhu et al, 2017 , Zhu et al, 2017 , Sadaf et al, 2017 , Sial et al, 2019a , Khan et al, 2019 ) they investigated that organic waste release of acidic decomposable compounds and decreased soil EC and pH. Whereas, biochar application increase soil EC and pH due its liming effects on soil environment ( Sial et al, 2019b , Sikdar et al, 2020 ). Biochar applications increased soil EC and pH ( Khan et al, 2019 ), liming effects ( Randolph et al, 2017 ) and alkalinity is a major aspect contributed liming potential ( Zhu et al, 2017 , Zhu et al, 2017 ), and caused increasing in soil EC and pH ( Sial et al, 2019d ).…”
Section: Resultssupporting
confidence: 60%
“…Similar, fluctuations were documented by incubation and pot experiment studies ( El-Mahrouky et al, 2015 , Zhu et al, 2017 , Zhu et al, 2017 , Sadaf et al, 2017 , Sial et al, 2019a , Khan et al, 2019 ) they investigated that organic waste release of acidic decomposable compounds and decreased soil EC and pH. Whereas, biochar application increase soil EC and pH due its liming effects on soil environment ( Sial et al, 2019b , Sikdar et al, 2020 ). Biochar applications increased soil EC and pH ( Khan et al, 2019 ), liming effects ( Randolph et al, 2017 ) and alkalinity is a major aspect contributed liming potential ( Zhu et al, 2017 , Zhu et al, 2017 ), and caused increasing in soil EC and pH ( Sial et al, 2019d ).…”
Section: Resultssupporting
confidence: 60%
“…Numerous studies have investigated the addition of organics including compost, biosolids, and organic-rich sludge to tailings for the purpose of mine reclamation, technosol formation, phytostabilization, and rehabilitation. The addition of organics to mine tailings has also been shown to induce biogeochemical processes such as sulfate reduction, which can immobilize elements of concern (e.g., As) through the precipitation of sulfide minerals . In this study, coupling organic and inorganic carbon cycling dramatically accelerated brucite carbonation, which is often limited by CO 2 supply.…”
Section: Resultsmentioning
confidence: 89%
“…PAL acts as the major enzyme for the conversion of L-phenyalanine into trans-cinnamic acid in the phenylpropanoid pathway, which subsequently produces phenolic compounds like phenols and flavonoids [ 13 , 53 , 54 ]. Our results revealed that PAL activity improved under stress conditions relative to the control plants ( Figure 6 A) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%